Smart analytics, artificial intelligence and sustainable performance management in a global digitalised economy. Part B - Tyagi, Pallavi; Grima, Simon; Sood, Kiran; Balusamy, Balamurugan; Özen, Ercan; Thalassinos, Eleftherios (Contemporary studies in economic and financial analysis ;, 2023)
The Covid 19 pandemic has created chaos in the business world and forced leaders to rethink their operational status quo. Balancing the physical and virtual spaces of the global digital economy wherein economic, commercial, and professional transactions are enabled by information and communication technologies has called for additional support from data-driven technologies like smart analytics and artificial intelligence. Opportunities created within digital economies to leverage technologies to execute tasks better, faster, and often differently have found the desired prominence in the recent past. Though the benefits outweigh the risks, the challenges in digitalised economies are as sophisticated as the solutions they offer. Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance. Both disciplinary and interdisciplinary studies are welcome.